A Profile of selected machine embroidery centers in Bocaue, Bulacan - Rantael, Jennifer Balagtas; Munda, Christine O. (Quezon City University of the Philippines Diliman, 2006)
The thesis entitled A Profile of Selected Machine Embroidery centers in Bocaue, Bulacan aimed to gather information regarding machine embroidery centers in Bocaue by looking into four aspects: organizational, technical/production, marketing and the common problems encountered by these centers. The study was done to provide a background on Bocaue's machine embroidery industry and to give the local government an concerned agencies an idea of the current status of these centers. The study was as well conducted to attract further studies on related garment cottage industries and to look unto these center's possible contribution to the local clothing and textile industry. The bulk of information on this study came from interviews with the owners of the respective machine embroidery centers. Majority of the respondents were located in Barangay Lolomboy and are into applying embroidery on knitted shirts. Based from the results of the study, it was concluded that these machine embroidery centers are at present experiencing financial difficulty and a decrease in quantity of job orders. According to the respondents, orders are shifted to factories abroad, which have the advantage of greater and faster rate of production at a lower cost. While their competitors are using modernized embroidery machines and are privileged to have a wide range of raw materials the local factories had to contend with their high-speed embroidery machines and low-quality raw materials. Most of them are disappointed on the lack of incentive from the government but they are still hoping that the government and other concerned agencies may find ways to strengthen their industry again. The selected embroidery centers that participated in this study believed that the support from the government and other other concerned agencies can enable them to expand and develop. It is recommended that an in-depth study on the u industry's status be made. A study on the design techniques and methods used on machine embroidery and how it can contribute to our local products is as well recommended.
Thesis (BSCT)--University of the Philippines Diliman
Keywords: Embroidery industry -- Philippines -- Bulacan